Teachers’ Self-efficacy Beliefs for Teaching Critical Thinking Skills and Practices of Its Strategies - Michael Amale; Abebe Gebretsadik (LET: Linguistics, Literature and English Teaching Journal)
The study aimed at exploring the teachers’ self-efficacy belief for teaching critical thinking skills and practices of strategies in reading classroom. It also pursued if there is any significant relationship between the two variables. A descriptive survey study used sequential explanatory mixed-methods approach to collect data.  The study involved 40 EFL teachers. The survey contained 19 items using five-point Likert scale. Qualitative data were collected via classroom observations. The results of quantitative data showed(m=3.3) that the participants implemented the strategies moderately. The findings of qualitative data revealed that most of critical thinking strategies were practiced rarely while participants were instructing reading lessons. However, the responsive strategy of teachers to their students’ responses was implemented better than others. Statistical analysis also disclosed a positive high significant correlation between the teachers’ self-efficacy belief for teaching CT and its implementation strategies during teaching reading lessons (r=0.99, p<0.05). In conclusion, as there was a positive strong correlation between teachers’ self-efficacy beliefs and actual classroom practice of strategies, teachers with strong self-confidence may have better experience in implementing strategies that improve students’ reading comprehension. This suggests that instructors’ strong beliefs to use critical thinking skills may not necessarily ensure its effective implementation of strategies.